EVALUASI KINERJA LAYANAN GLAMPING BUKIT LINTANG SEWU BANTUL BERDASARKAN INDIKATOR SAPTA PESONA - Nursiana, Adinoto; Rohman, Nur; Sutrisno, Sutrisno; Kiswantoro, Amin; Budhijono, Fongnawati (Kepariwisataan: Jurnal Ilmiah, 2025)
AbstractGlamping, a blend of hotel comfort and camping experience, has emerged as a popular nature-based tourism trend. Bukit Lintang Sewu Glamping in Bantul, Yogyakarta, offers natural attractions but requires risk management to ensure safety, comfort, and service reliability. This study aims to identify operational service aspects needing improvement and those providing competitive advantages, based on the Sapta Pesona concept. Conducted in 2024 at Bukit Lintang Sewu, Bantul, the research employed a mixed-method QUAN+qual approach, involving 100 tourists aged ≥17 years and interviews with managers and local residents. Data were analyzed using Importance Performance Analysis (IPA). Results show that only 28% of the 36 measured indicators meet tourist needs, while 11% require urgent improvement, particularly in Safety and Memory aspects, such as jogging tracks, infrastructure maintenance, Wi-Fi reliability, and suggestion boxes. Ten indicators performed well, four had low performance with low importance, and fifteen were considered excessive. In conclusion, management should prioritize improving basic health facilities, cleanliness, infrastructure upkeep, and staff responsiveness. Recommendations include regular evaluations, staff skill enhancement, and optimizing visitor feedback to maintain glamping sustainability and competitiveness. Future research should expand to other glamping sites in Yogyakarta and across Indonesia to identify broader improvement priorities.Keywords:  Glamping; Sapta Pesona; Importance Performance Analysis; Risk Management; Bukit Lintang SewuAbstrakGlamping menjadi tren wisata alam yang menggabungkan kenyamanan hotel dengan pengalaman berkemah. Glamping Bukit Lintang Sewu di Bantul, Yogyakarta, menawarkan daya tarik alam, namun memerlukan pengelolaan risiko untuk menjamin keamanan, kenyamanan, dan kepastian layanan. Penelitian ini bertujuan mengidentifikasi aspek layanan operasional yang memerlukan perbaikan dan yang menjadi keunggulan kompetitif, berdasarkan konsep Sapta Pesona. Penelitian dilakukan di Bukit Lintang Sewu, Bantul pada 2024, menggunakan metode campuran QUAN+qual dengan 100 responden wisatawan berusia ≥17 tahun, serta wawancara dengan pengelola dan masyarakat sekitar. Data dianalisis menggunakan Importance Performance Analysis (IPA). Hasil menunjukkan dari 36 indikator, hanya 28% memenuhi kebutuhan wisatawan, 11% memerlukan perbaikan segera, khususnya pada unsur Aman dan Kenangan, seperti jogging track, keterawatan infrastruktur, kehandalan Wi-Fi, dan kotak saran. Sepuluh indikator berkinerja baik, empat berkinerja rendah dengan kepentingan rendah, dan lima belas dianggap berlebihan. Kesimpulannya, pengelola perlu fokus pada peningkatan fasilitas kesehatan dasar, kebersihan, pemeliharaan infrastruktur, serta responsivitas staf. Disarankan evaluasi berkala, peningkatan keterampilan petugas, dan optimalisasi umpan balik pengunjung untuk menjaga keberlanjutan dan daya saing glamping. Penelitian selanjutnya dapat diperluas ke glamping lain di Yogyakarta dan wilayah lain di Indonesia.Kata Kunci:  Glamping; Sapta Pesona; Importance Performance Analysis; Manajemen Risiko; Bukit Lintang Sewu